Pengaruh Tingkat Pendapatan dan Jumlah Anggota Keluarga Terhadap Kesejahteraan Keluarga Buruh Tani di Desa Ambengan Kecamatan Sukasada Kabupaten Buleleng - Komang Septia Tri Widari; Made Ary Meitriana (Ekuitas: Jurnal Pendidikan Ekonomi, 2025)
This study aims to determine the effect of income level and number of family members on the welfare of farm laborers' families in Ambengan Village, Buleleng Regency. This study uses a quantitative method with a causality research type. The population of this study was 100 rice farm laborers. The sampling technique used was accidental sampling, with a sample size of 80 respondents. The type of data used is quantitative data. The data sources used are primary and secondary data. Data analysis in this study used multiple linear regression analysis techniques. Hypothesis testing was carried out using the t-test and F-test with a significance level of 5%. The results of the study showed that: (1) income has a positive and significant effect on the welfare of farm laborers' families in Ambengan Village, Buleleng Regency, (2) the number of family members has a negative and significant effect on the welfare of farm laborers' families in Ambengan Village, Buleleng Regency, and (3) Simultaneously, income and number of family members have a positive and significant effect on the welfare of farm laborers' families in Ambengan Village, Buleleng Regency.